Hepatic pyruvate and alanine metabolism are critical and complementary for maintenance of antioxidant capacity and resistance to oxidative insult - Nicole K.H. Yiew; Joel H. Vazquez; Michael R. Martino; Stefanie Kennon-McGill; Jake R. Price; Felicia D. Allard; Eric U. Yee; Alexander J. Layman; Laura P. James; Kyle S. McCommis; Brian N. Finck; Mitchell R. McGill (Elsevier, 2023)
Objective: Mitochondrial pyruvate is a critical intermediary metabolite in gluconeogenesis, lipogenesis, and NADH production. As a result, the mitochondrial pyruvate carrier (MPC) complex has emerged as a promising therapeutic target in metabolic diseases. Clinical trials are currently underway. However, recent in vitro data indicate that MPC inhibition diverts glutamine/glutamate away from glutathione synthesis and toward glutaminolysis to compensate for loss of pyruvate oxidation, possibly sensitizing cells to oxidative insult. Here, we explored this in vivo using the clinically relevant acetaminophen (APAP) overdose model of acute liver injury, which is driven by oxidative stress. Methods: We used pharmacological and genetic approaches to inhibit MPC2 and alanine aminotransferase 2 (ALT2), individually and concomitantly, in mice and cell culture models and determined the effects on APAP hepatotoxicity. Results: We found that MPC inhibition sensitizes the liver to APAP-induced injury in vivo only with concomitant loss of alanine aminotransferase 2 (ALT2). Pharmacological and genetic manipulation of neither MPC2 nor ALT2 alone affected APAP toxicity, but liver-specific double knockout (DKO) significantly worsened APAP-induced liver damage. Further investigation indicated that DKO impaired glutathione synthesis and increased urea cycle flux, consistent with increased glutaminolysis, and these results were reproducible in vitro. Finally, induction of ALT2 and post-treatment with dichloroacetate both reduced APAP-induced liver injury, suggesting new therapeutic avenues. Conclusions: Increased susceptibility to APAP toxicity requires loss of both the MPC and ALT2 in vivo, indicating that MPC inhibition alone is insufficient to disrupt redox balance. Furthermore, the results from ALT2 induction and dichloroacetate in the APAP model suggest new metabolic approaches to the treatment of liver damage.